Defining civil and political rights : the jurisprudence of the United Nations Human Rights Committee - Conte, Alex, 1971- (Ashgate, 2009)
"Defining Civil and Political Rights provides a comprehensive analysis and commentary on the decisions - technically known as views - of the United Nations Human Rights Committee, for use by human rights lawyers throughout the world. Each of the substantive rights and freedoms set out in the International Covenant on Civil and Political Rights is considered in detail, by analysis of final reviews and comments of the Human Rights Committee." "This second edition has been thoroughly revised and updated to take account of recent jurisprudence on the Human Rights Committee. New material has been added based upon substantive areas of the committee's jurisprudence."--BOOK JACKET.